Electronic and photocatalytic properties of ZnO/GaTe heterostructure from first principles calculations. (February 2023) - Li, Lingxia; Guo, Xin; Lu, Xuefeng; Ren, Junqiang; La, Peiqing
Abstract: Constructing a novel van der Waals (vdW) heterostructure by integrating diverse two-dimensional (2D) materials is significant to generate the more fascinating performances. In this present contribution, the electronic and photocatalytic properties of ZnO/GaTe heterostructure have been explored using first-principles calculations. The results reveal that the interaction between layers is dominated by the vdW forces. It displays an intrinsic type-II band alignment and a direct band gap of 1.730 eV under hybrid HSE06 functional. The valence band top and conduction band bottom are located at ZnO and GaTe layers, respectively, which guarantees the spatial separation of photogenerated electron-hole pairs and improves the photocatalytic efficiency. Moreover, the band edges all span the energy levels of both the reduction and oxidation potentials of H2 O, indicating that its better photocatalytic performance. The modulated photocatalytic properties under varied pH circumstances imply that an acid environment is more favorable to the water splitting process. Furthermore, the band edge alignment exhibits the significant adjustability through varying vertical and in-plane biaxial strains. These theoretical findings indicate that the ZnO/GaTe heterostructure can offer an alternative strategy to design the efficient photocatalysts for water splitting.